FINANCIAL KNOWLEDGE AND FINANCIAL BEHAVIOR: THE ROLE OF SELF-EFFICACY AND FINANCIAL ATTITUDES - Hidayat, Taufik; Fikri, Muhammad Ali; Kusuma, Desta Rizky (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Young people are vulnerable people with various problems, especially financial problems. To overcome financial problems, individuals must understand well about financial knowledge, self-efficacy, financial attitudes and also financial behavior. Researchers wanted to analyze the role of self-efficacy and financial attitudes on the effect of financial knowledge on financial behavior. The respondents of this study were generation Z in Yogyakarta with a sample of 80 respondents. Data from respondents were processed with the Structural Equation Model (SEM) with the Smart PLS 4.0 statistical tool. The results of this study show that financial knowledge has an effect on financial behavior, self-efficacy mediates the effect of financial knowledge on financial behavior, financial attitudes mediate the effect of financial knowledge on financial behavior.